2014
DOI: 10.1007/s00253-013-5459-8
|View full text |Cite
|
Sign up to set email alerts
|

Domain C of thermostable α-amylase of Geobacillus thermoleovorans mediates raw starch adsorption

Abstract: The gene (1,542 bp) encoding thermostable Ca(2+)-independent and raw starch hydrolyzing α-amylase of the extremely thermophilic bacterium Geobacillus thermoleovorans encodes for a protein of 50 kDa (Gt-amyII) with 488 amino acids. The enzyme is optimally active at pH 7.0 and 60 °C with a t 1/2 of 19.4 h at 60 and 4 h at 70 °C. Gt-amyII hydrolyses corn and tapioca raw starches efficiently and therefore finds application in starch saccharification at industrial sub-gelatinisation temperatures. The starch hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…5 to 7 (1). The functions of CBM25 domains have been described previously, and their three-dimensional (3D) structures have been resolved (30,(44)(45)(46). It has also been demonstrated that the CBM25-26 tandem in the maltohexaose-forming amylase from Bacillus halodurans C-125 has a 50-fold stronger binding affinity for granular corn starch than each of the single domains (44).…”
Section: Discussionmentioning
confidence: 95%
“…5 to 7 (1). The functions of CBM25 domains have been described previously, and their three-dimensional (3D) structures have been resolved (30,(44)(45)(46). It has also been demonstrated that the CBM25-26 tandem in the maltohexaose-forming amylase from Bacillus halodurans C-125 has a 50-fold stronger binding affinity for granular corn starch than each of the single domains (44).…”
Section: Discussionmentioning
confidence: 95%
“…This observation leads to the idea that Trp201 and Trp202 of BaqA might represent a fingerprint of the new GH13 α-amylase subfamily [69]. These two tryptophans are also conserved in Geobacillus thermoleovorans α-amylases GTA [73] and Gt-amyII [61] as W204 and W205 with an important difference that in these two cases W205 is not located on the surface of the protein but hidden within the structure. On the other hand, the role of domain C in raw starch adsorption has been proven by truncation and LangmuirHinshelwood adsorption experiments [61].…”
Section: Industrial Aspects Of Rsda Application In Raw Starch Hydrolysismentioning
confidence: 99%
“…There are not many α-amylases that are able to perform effectively on high concentration of raw starch (>25%) [28, [60][61][62][63][64][65] (Table 1), due to substrate or product inhibition [66] and because of the need for higher enzyme concentrations in raw starch digestion, which have to be obtained through the optimized upstream and downstream processing to obtain high quantity of biocatalyst. It is likely that during amylase attack on starch granule, enzymestarch physical, irreversible or non-catalytic binding may be both, productive and non-productive, which is why high enzyme loadings give rise to the formation of productive interactions [8].…”
Section: Industrial Aspects Of Rsda Application In Raw Starch Hydrolysismentioning
confidence: 99%
See 2 more Smart Citations